Phosphorylated IRF3 promotes GSDME-mediated pyroptosis through RIPK1/FADD/caspase-8 complex formation during mitotic arrest in ovarian cancer - Wenjian Gong; Dongchen Zhou; Qiuyang Xu; Linghui Wang; Mengshi Luo; Yuewen Zhang; Zhiqi Liao; Fan Xiong; Guangnian Zhao; Bingbing Zhao; Qinglei Gao; Yong Fang (Cell Communication and Signaling)
Abstract Inducing mitotic arrest with anti-mitotic drugs is an effective strategy for cancer therapy. However, the ultimate fate of cells that undergo prolonged mitotic arrest remains largely uncertain. In this study, paclitaxel and nocodazole were used to induce prolonged mitotic arrest in ovarian cancer cells, triggering mitotic catastrophe, during which these cells exhibited hallmarks of pyroptosis. Subsequently, small interfering RNA (siRNA)-mediated downregulation of Gasdermin E (GSDME) inhibited pyroptosis, suggesting that GSDME plays an essential role in this process. The upstream signaling pathway was further investigated through caspase-3 inhibition and caspase-8 knockdown, which demonstrated that pyroptosis induced by paclitaxel and nocodazole was mediated by the caspase-8/caspase-3/GSDME pathway. Moreover, during mitotic arrest, phosphorylation of IRF3, mediated by cGAS/TBK1, led to the formation of the RIPK1/FADD/caspase-8 complex, which subsequently activated caspase-8 and initiated downstream GSDME-mediated pyroptosis. Knockdown of components of this complex or mutation of the IRF3 phosphorylation site inhibited pyroptosis. Furthermore, in vivo experiments also demonstrated that paclitaxel inhibited tumor growth by inducing GSDME-mediated pyroptosis and activating the anti-tumor immune infiltration. TCGA data further suggested that ovarian cancer cases treated with paclitaxel, showing high expression of GSDME and caspase-3, exhibited a more favorable tumor immune microenvironment. This study not only elucidated the specific mechanism of pyroptosis mediated by phosphorylated IRF3 during prolonged mitotic arrest but also revealed that mitotic arrest-induced pyroptosis could enhance immune infiltration in ovarian cancer, providing valuable insights for clinical treatment strategies.